Integrating AI-generated client simulations in architectural education - Gunagama, M. Galieh; Fildzah Zatalini Zakirah (Refleksi Pembelajaran Inovatif, 2025)
This study examines the integration of AI-generated client simulations to address a critical gap in architectural education: the limited exposure to unpredictable, human-centric client dynamics in traditional studio pedagogy. Conducted within the Integrated Design Studio (IDS) at Universitas Islam Indonesia, the research employed ChatGPT to generate randomized client profiles across seven categories for 10 students. Qualitative and quantitative analyses revealed that AI simulations significantly enhanced students’ adaptability, creativity, and critical thinking, compelling them to resolve "cultural-programmatic collisions." While realism in simulating human unpredictability scored moderately, the tool fostered deep contextual engagement, evidenced by students’ score gains in technical integration for resolvable conflicts. However, irreconcilable constraints hindered technical synthesis, underscoring the need for calibrated complexity. The study concludes that AI-generated profiles bridge theoretical pedagogy and real-world practice but require scaffolding to mitigate cognitive overload and augment socio-emotional depth. Recommendations include tiered complexity filters and hybrid models blending AI with live client interactions.